Cartelization through buyer groups - Chris Doyle; Martijn A. Han (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Retailers may enjoy stable cartel rents in their output market through the formation of a buyer group in their input market. A buyer group allows retailers to credibly commit to increased input prices, which serve to reduce combined final output to the monopoly level; increased input costs are then refunded from suppliers to retailers through slotting allowances or rebates. The stability of such an implied cartel depends on the retailers' incentives to secretly source from a supplier outside of the buyer group arrangement at lower input prices. Cheating is limited if retailers sign exclusive dealing or minimum purchase provisions. We discuss the relevancy of our findings for antitrust policy.
Keywords: K21; L13; L41; L42; 330; buyer groups; collusion; exclusive dealing; minimum purchase clauses; rebates; Einkaufsgemeinschaft; Einzelhandel; Wettbewerbsbeschränkung; Kartell; Rabatt; Lieferanten-Kunden-Beziehung; Theorie